ANALISIS DAN PERANCANGAN SISTEM PENGOLAHAN DATA PADA BENGKEL DISTRO BAN - Charolina, Astri; Retnoningsih, Dwi; Asniati, Diana Nur (JURNAL GAUNG INFORMATIKA, 2015)
Distro Ban is a store that specializes in selling motorcycle spare parts and services for the motor servicing. This shop every day to meet the needs of consumers,so the sale is the main thing in the store. Distro Ban in data processing workshop servicing and spare parts are still using manual way. All incoming and outgoinggoods data is recorded in the books, so the possibility of errors in the calculation and the  availability of existing stocks become inaccurate.Then design and analysis a system of data processing applications in the workshop and spare parts Distro Ban distributions computerized web-based php. Theaim of this study is to design and analysis the transaction systems and computerized data items. The benefit is that the data produced is more accurate, effective andreduce errors in the reporting of data as well as to monitor the inventory of existing stock. Data collection methods used were interviews, observation and library research.